Negotiating the TRIPS Waiver Proposal: India’s Strategy in the WTO to Tackle COVID-19 Pandemic - Ari Camila Puspa Devi (Journal of World Trade Studies, 2024)
This research examines India's negotiation strategy on the proposal to waive the TRIPS Agreement (TRIPS waiver) at the WTO to deal with COVID-19. India, along with South Africa, submitted the TRIPS waiver proposal in response to the disparity of available medicines between developing and developed countries during the COVID-19 pandemic in 2020. India has played an important role in proposing TRIPS waiver in 2020. India’s historical legacy to the birth of TRIPS flexibility during the Uruguay Round 1989 and the Doha Declaration on TRIPS and Public Health during the Doha Round 2001, making it interesting to observe the dynamics of negotiation and strategies used to include the TRIPS waiver in the Ministerial Conference 12. This research demonstrates that India has failed to use mixed-distributive strategy during the negotiation and then it shifts to apply integrative strategy due to the Quadrilateral type of negotiation, tight deadline affected by negotiation deadlock, and pressure of green room negotiation during the TRIPS waiver negotiation. The research utilizes the concepts of distributive and integrative strategy, as well as the dual concern model, to identify India's strategy and elaborate transformation. This research aims to contribute to the discussion of how developing countries like India navigate multilateral trade negotiation in WTO amidst contested interest between the Global North and South and elaborating strategy used during the process of negotiation.